Inversión pública y crecimiento económico de la región Loreto en el periodo 2007 - 2019 - Pfenning Venturi, Estela Yajaira (2021)
The research is entitled "Public Investment and Economic Growth of the Loreto Region in the 2007 - 2019 Period" and its general objective is to determine the relationship between public investment and economic growth of the Loreto Region in the 2007 - 2019 period. Our variables: Gross Value Added, dependent variable, and public investment, independent variable, will have as study period the years from 2007 to 2019. Through the theoretical framework, we consolidate the importance of public investment and its behavior with respect to economic growth. After processing and analyzing the data collected, the results we obtain show us that in the case of Gross Value Added its behavior is upward and in the case of public investment the behavior is upward as well; that is, it has a proportional increase every year, which means that it is a positive correlation. In conclusion, with the analysis, it was possible to verify that public investment affects economic growth in the Loreto region for the period 2007 - 2019.